2014
DOI: 10.1016/j.expneurol.2013.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Non-mammalian model systems for studying neuro-immune interactions after spinal cord injury

Abstract: Mammals exhibit poor recovery after injury to the spinal cord, where the loss of neurons and neuronal connections can be functionally devastating. In contrast, it has long been appreciated that many non-mammalian vertebrate species exhibit significant spontaneous functional recovery after spinal cord injury (SCI). Identifying the biological responses that support an organism's inability or ability to recover function after SCI is an important scientific and medical question. While recent advances have been mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 195 publications
0
21
0
Order By: Relevance
“…Indeed, many studies use astrocytic boundaries to demarcate regions of frank tissue pathology from more intact penumbral tissues [45]. This interface is sometimes referred to as the Bglia limitans.^The strict sequestration of cell types is in stark contrast to regenerating species where both ECM components and glial cells cross the lesion site and precede neural regeneration [46][47][48]. Formation of the glia limitans may be species-specific or driven by cellular interactions, as the phenomenon has been replicated in vitro by cocultures of mammalian astrocytes and fibroblasts/ Schwann cells that maintain spatial separation and inhibit neurite growth [11,21,42].…”
Section: Glial and Fibrotic Scarring After Spinal Cord Injurymentioning
confidence: 99%
“…Indeed, many studies use astrocytic boundaries to demarcate regions of frank tissue pathology from more intact penumbral tissues [45]. This interface is sometimes referred to as the Bglia limitans.^The strict sequestration of cell types is in stark contrast to regenerating species where both ECM components and glial cells cross the lesion site and precede neural regeneration [46][47][48]. Formation of the glia limitans may be species-specific or driven by cellular interactions, as the phenomenon has been replicated in vitro by cocultures of mammalian astrocytes and fibroblasts/ Schwann cells that maintain spatial separation and inhibit neurite growth [11,21,42].…”
Section: Glial and Fibrotic Scarring After Spinal Cord Injurymentioning
confidence: 99%
“…Functional recovery after spinal cord injury in lampreys and other non-mammalian vertebrates is supported by extensive regeneration of descending axons beyond the lesion scar (Bloom, 2014; Morgan and Shifman, 2014). Previous studies in lampreys reported that 30-70% of descending reticulospinal axons regenerated several millimeters beyond the lesion center by 11 wpi (Yin and Selzer, 1983; Davis and McClellan, 1994; Oliphint et al, 2010; Lau et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As examples, zebrafish and amphibians can regenerate parts of their retina, optic nerve, and brain (Sperry, 1947; Fawcett and Gaze, 1981; Vergara and Del Rio-Tsonis, 2009; Goldshmit et al, 2012; Gorsuch and Hyde, 2014; Morgan and Shifman, 2014; Williams et al, 2015). Species ranging from lampreys and fishes to amphibians and reptiles can regenerate spinal cord structures (Tanaka and Ferretti, 2009; Zukor et al, 2011; Goldshmit et al, 2012; Diaz Quiroz and Echeverri, 2013; Bloom, 2014; Morgan and Shifman, 2014). Although central nervous system (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The response of central nervous system (CNS) neurons to spinal cord injury is a complex process with intrinsic neuronal changes that may or may not lead to upregulation of regeneration‐associated genes as well as extrinsic events that include invasion of fibroblasts, activation of resident glial cells (Bignami, Forno, & Dahl, ; Busch & Silver, ; Fitch & Silver, ) and an immune response with recruitment of hematogenous cells (Bloom, ; Cregg et al, ; Donnelly & Popovich, ; Fawcett, ; Gaudet et al, ; Jablonski, Gaudet, Amici, Popovich, & Guerau‐de‐Arellano, ; Kawano et al, ; London, Cohen, & Schwartz, ; Neirinckx et al, ; Popovich, ; Schwab, Zhang, Kopp, Brommer, & Popovich, ). The interaction of intrinsic and extrinsic factors most likely determines whether a particular neuron will sprout neurites, regrow its axon and possibly undergo functional regeneration (Becker & Becker, ; Ferguson & Son, ; Silver, Schwab, & Popovich, ).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of resident immune cells in the CNS precedes the attraction of peripheral immune cells into the wound site as part of the innate and adaptive immune responses (reviewed in Bloom, 2014;Brennan & Popovich, 2018). Generally, neutrophils, granular leukocytes, and monocytes arrive at the wound within hours to days followed later by lymphocytes (Gadani, Walsh, Lukins, & Kipnis, 2015).…”
mentioning
confidence: 99%